LINTAS SEJARAH DAN RAGAM PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI (FORMAL, NON FORMAL, INFORMAL) - Saudah Saudah (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2015)
Children are a gift of God which is given to be treated and maintained. Oneeffort to give attention to early childhood is the provision of a decent education tochildren, especially during the development of the child, so the child is able tomaximize its development to the optimum. an early age is an important phase inhuman development across the life span. the attention of parents to their childrenwill determine how the child in adult life. to provide educational services for earlychildhood can be started since the child is born until the age of 6 years. thegovernment has set up the organization for early childhood: first, formal channelsinclude kindergarten (TK), Raudhatul RA (RA) and kindergarten outstanding(TKLB). A second, non-formal pathways include garden Nursery (TPA), play group(KB) and a type of early childhood education Units (SPS), and the third informalchannels such as family education and the environment. This type of service devotedto early childhood is intended to prepare children to enter further education.Keywords: Early Childhood Education(ECD), Formal, Formal, Informal